2022
DOI: 10.7759/cureus.21792
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Team-Based Learning Over Conventional Didactic Lecture Among Second-Year MBBS Students

Abstract: Team-based learning (TBL) is an active and structured learning process. This study was undertaken to develop interest among the students over the subject and to analyze the academic performance over routine conventional lecture method of teaching. This was a comparative study organized to know the effectiveness of TBL over conventional didactic lecture (CDL) and also to assess the student's perception towards TBL. MethodsThis was an interventional study where second-year MBBS students took part. Students were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In this study, we found no significant difference between the two methods as the p-value obtained was more than .05, whereas S. Rajeswarie et al, in their study, compared team-based learning over conventional didactic lecture and found that the academic performance of the students was better for team-based learning as compared to those who had undergone conventional didactic lecture. The p-value obtained was also statistically significant for the team-based learning method [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no significant difference between the two methods as the p-value obtained was more than .05, whereas S. Rajeswarie et al, in their study, compared team-based learning over conventional didactic lecture and found that the academic performance of the students was better for team-based learning as compared to those who had undergone conventional didactic lecture. The p-value obtained was also statistically significant for the team-based learning method [ 19 ].…”
Section: Discussionmentioning
confidence: 99%